The Influence of Non Performoing Loan, Third Party Fund, Credit Growth, and Credit Risk on Profitability - Sherlita, Erly; Haizam Mohd Saudi, Mohd (International Journal of Psychosocial Rehabilitation, 2020)
This research aims to test the influence of the third-party funds, credit growth, and credit risk on profitability in banking listed on the Indonesian stock exchange for the period 2016-2018. The data used are secondary data. Sample withdrawal technique using census techniques that use the entire population. This study is the explanatory research. The data analysis used is a regression analysis of data panels. The results show that the variables of third-party funds, credit growth, and credit risk have influence on return on asset. The results on the determination of the coefficient in the regression model show that the influence of variables third-party funds, credit growth, and credit risk on profitability is 51%, while the rest of 49% is explained by variables other than the regression model.